El efecto de la educación en la tasa de criminalidad: un panel de datos para los departamentos de la sierra del Perú 2012 al 2017 - Cotera Caparachin, Henry Rogelio (2022)
The present investigation uses data from crime rate panels for a group of departments in Peru for the period from 2012 to 2017, based on data from the National Institute of Statistics and Informatics, the annual crime reports of the National Police of Peru and the Ministry of Health of Peru, to analyze the relationship between education and the crime rate both between departments and over time; likewise, victimization was produced as a crime rate. The methodology used is Feasible Generalized Least Squares, to solve heteroskedasticity problems. The results mainly show that the level of education achieved had a negative impact on the crime rate.